2018
DOI: 10.1007/s10714-018-2375-3
|View full text |Cite
|
Sign up to set email alerts
|

Strong lensing of a regular black hole with an electrodynamics source

Abstract: In this paper we have investigated the gravitational lensing phenomenon in the strong field regime for a regular, charged, static black holes with non-linear electrodynamics source. We have obtained the angle of deflection and compared it to a Schwarzschild black hole and Reissner Nordström black hole with similar properties. We have also done a graphical study of the relativistic image positions and magnifications. We hope that this method may be useful in the detection of non-luminous bodies like this curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In the strong field limit of arbitrary statics and spherically symmetric (SSS) spacetime, Bozza [43] developed a general method to calculate the deflection angle for lightrays and showed that it always diverges logarithmically as ln(x − x 0 ) where x 0 is the closest approach of the ray. Many authors successfully calculated the deflection angles in the strong field limit for particular spacetimes using this method [41,[44][45][46][47]. However, from an observational point of view, all the light bending and GLs seen up to now are in the weak field limit, i.e., with small deflection angles.…”
Section: Introductionmentioning
confidence: 99%
“…In the strong field limit of arbitrary statics and spherically symmetric (SSS) spacetime, Bozza [43] developed a general method to calculate the deflection angle for lightrays and showed that it always diverges logarithmically as ln(x − x 0 ) where x 0 is the closest approach of the ray. Many authors successfully calculated the deflection angles in the strong field limit for particular spacetimes using this method [41,[44][45][46][47]. However, from an observational point of view, all the light bending and GLs seen up to now are in the weak field limit, i.e., with small deflection angles.…”
Section: Introductionmentioning
confidence: 99%
“…Strong deflection case on the other hand, is used for another problems: for example, for investigations of so-called relativistic images. To this end, we wish to point out the strong gravitational lensing for the Schwarzschild black hole [5,6], then extended to the Reissner-Nordstr öm black hole [7,8], regular black holes [9], and wormholes [10][11][12][13], while the investigations of so-called relativistic images see also Refs. [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, micro GL is worked on the bases of strong GL, in which the image separation is too small to be resolved. Gravitational lensing is processed in different space times in different ways [12][13][14][15][16][17]. Moreover, in past years, many studies have related GL with the Gauss-Bonnet theorem (GBT) after Gibbons and Werner's conformation of the useful method for calculating the bending angle of BHs that shows asymptotic behaviour [18], which is given as:…”
Section: Introductionmentioning
confidence: 99%